2020
DOI: 10.12700/aph.17.3.2020.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Design and Construction of a Sun Simulator for Laboratory Testing of Solar Cells

Abstract: The current study is dedicated to the realization and development of an ASTM E972 standardized, class C sunlight simulator. Sunlight simulators or sun simulators are laboratory devices used to study solar cells. Our sun simulator is suitable for the examination and qualification of solar cells, with an area of 150 mm x 150 mm. It consists of 4 LED blocks of different colors and a halogen reflector. The completed sun simulator is validated; the design and realized parameters display good matching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…This lab is designed to serve students and researchers with experimental learning on solar microgrids. István et al [11] developed a solar simulator for a university laboratory and experimentally demonstrated that the fabricated system is on par with a commercial one, with a satisfactory measurement error (±0.022%).…”
Section: Energy Laboratory Development In Universitiesmentioning
confidence: 99%
“…This lab is designed to serve students and researchers with experimental learning on solar microgrids. István et al [11] developed a solar simulator for a university laboratory and experimentally demonstrated that the fabricated system is on par with a commercial one, with a satisfactory measurement error (±0.022%).…”
Section: Energy Laboratory Development In Universitiesmentioning
confidence: 99%
“…As a precursor to this research, a standard solar simulator was developed. Requirements for solar simulators are managed by American Standard for Testing and Materials (ASTMs) E972 (IEC 60904-9) [1]. The solar simulator implemented in the current research is a standard Class C, so both spatial non-uniformity and temporal non-uniformity are below 10%.…”
Section: The Experimental Compositionmentioning
confidence: 99%
“…The temperature of the solar cell is controlled by a cooling module made using Peltier modules [1]. The temperature of the solar cell is measured by a Voltcraft PL-125-T4 four-channel digital thermometer, furthermore current and voltage measurements are performed by two METEIX MX 59H digital multimeters.…”
Section: The Experimental Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…These simulators usually use LED lights, [4][5][6][7] xenon-based lights, [8][9][10][11] or QTH lamps. 12,13 Gheorghian et al 14 proposed a solar simulator that uses two different lights sources: four floodlights halogen lamps and two lamps arrangements, both of them capable of producing a nonuniformity of irradiance under 10% over an area of 31 × 31 cm 2 . Salam et al 15 developed a solar simulator based on QTH lamps filtering part of the infrared spectrum with a water tank diluted with blue dye placed between the light source and the SPVM.…”
mentioning
confidence: 99%